Biopesticide potential of phytochemical extracts from the nut of Areca catechu L. against mango fruit anthracnose - Ahmad Rusdan, Aizad Izha (2014)
Anthracnose is an important disease that attacks mangoes in Malaysia and many other regions. It is caused by a fungal known as Colletotrichum gloeosporioides. The disease has caused devastating effects on the post-harvest where mangoes are already infected. The application of fungicides is a common method use in controlling the infection of this disease; however, the usage brings negative effects on our environment and may affect the health of consumers as well. One of the potential alternatives to replace or reduce the use of fungicides is by applying natural extracts from plants. The nut of Areca catechu, which is also known as betel nut, is a potential to be explored as a natural antifungal agent. This exotic plant is native to the Southeast Asia region where it is available abundantly. The nut of A.catechu contains stimulant that was traditionally used (or chewed) with betel leaves during past-time especially by people in certain parts in Asia. The nut was also traditionally used as medicine to treat diseases in many cultures in Asia Pacific. For the purpose of exploring the potential of the nut as a natural antifungal agent, this study was conducted by applying its natural extracts to treat anthracnose disease on mangoes. Six extracts (namely, hexane, chloroform and methanol extracts) from ripe and unripe nuts of A.catechu were tested in antifungal screening tests against mycelium growth and spores germination of C.gloeosporioides. Among all the extracts, the chloroform extract from the unripe nuts (at the concentration of 10.0 mg/mL) gave best antifungal reaction by inhibiting about 52% of mycelium growth and 100% of spore germination. Compound screening carried out on that particular extract revealed that it contained both alkaloids and phenolics which are important and most studied substances in the nut of A. catechu. Both substances could cause antifungal activities and might be responsible in controlling the growth development of C. gloeosporioides in the study. Based on the results in antifungal screening tests, the chloroform extract from the unripe nut at the concentration of 10 mg/mL was selected to be applied on mango in in vivo test with the purpose to treat anthracnose disease. Thus, this particular extract was selected to treat the fruit against anthracnose in two different ways, namely, by dipping them in the extract solution at 27oC for one hour (normal dip) and also at 52oC for five minutes (hot dip). Meanwhile, control and benomyl solutions (each applied in both dipping methods) were used as comparisons. The testproved that the treatment using the extract reduced 34% of disease infection and 27% of disease rate from control. However, the treatment using benomyl was slightly effective compared tousing the extract, reducing around 47% of disease infection and 38% of disease rate from control. Hence, results from test also proved that the treatment applied at 52oC was more effective than those conducted at 27oC,wheretreatment at 52oC reduced 51% of disease infection and 35% of disease rate from treatment applied at 27oC. Based on the results in in vivo test, post-harvest quality of fruit treated by dipping inside extract solution at 52oC for five minutes was analysed.Results from the analysis showed that the treatment increased shelf life by slowing down the ripening process. The parameters analysed included physical characteristics of the fruits (weight loss, firmness, and external peel colour), whereas the parameters for the chemical characteristics analysed were titratable acidity, pH, soluble solid concentration, and ascorbic acid concentration. It is hoped that the extract can be a potential alternative for chemical fungicides to control plant diseases and improve the shelf life of fruit.